The Influence of School Leadership and Work Motivation toward Teacher’s Discipline - Darmiati, Darmiati; Kristiawan, Muhammad; Rohana, Rohana (Journal of Social Work and Science Education, 2020)
This study determined the effect of school leadership on the work discipline of teachers in Madrasah Tsanawiyah Negeri Ogan ilir. This research used quantitative methods with correlational types. Data were collected using a questionnaire. Data were analyzed using simple linear regression test analysis techniques and multiple linear regression. The results showed that 1) principal's leadership has a significant effect on teacher discipline; 2) work motivation has a significant effect on teacher discipline; and 3) principal's leadership and work motivation together have a significant effect on the work discipline.